2019
DOI: 10.15421/2019_94
|View full text |Cite
|
Sign up to set email alerts
|

Post-harvest siderates impact on the weed littering of Maize

Abstract: The problem of post-harvest winter rapeseed crops usage influencing siderate and green fodder, oil radish impacting siderate and forage, root and post-harvest remains of winter wheat, and also cattle manure (40 t/ha) influencing the weed littering of maize and grain under conditions of grain-cultivated crop rotation has been revealed by PS of NUBiP of Ukraine - Agronomic research station. It has been proved that the cleanest crops of maize on the typical low-humus and light-loamy black soils remained in the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…In the experiment was sown Camelina sativa variety Hirsky of selection Ivano-Frankivsk Institute AIP NAAS included in the State Register of varieties suitable for cultivation in Ukraine and adapted to the conditions of the Carpathians. The seed yield stated in the patent is on average 2.1 t.ha -1 , green mass -40.5 t.ha -1 (Abramyk et al, 2003;Karpenko et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…In the experiment was sown Camelina sativa variety Hirsky of selection Ivano-Frankivsk Institute AIP NAAS included in the State Register of varieties suitable for cultivation in Ukraine and adapted to the conditions of the Carpathians. The seed yield stated in the patent is on average 2.1 t.ha -1 , green mass -40.5 t.ha -1 (Abramyk et al, 2003;Karpenko et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Microorganisms synthesize various physiologically active compounds (antibiotics, plant toxins, stimulants and inhibitors of growth), take active part in conversion of physiologically active substances secreted by plants and microorganisms into compounds more active than the original ones [Bater, 1996; Growing post-harvest siderates has a multifaceted positive effect on soil properties (enriches the primer with nitrogen and organic matter). Post-harvest siderates reduce soil acidity, decrease the mobility of aluminum, and increase the buffer capacity of absorption [Karpenko et al, 2019;Karpenko et al, 2020b;Scherner et al, 2016]. When plowing the green mass of plants, the structure of the soil improves, the volume mass of the arable layer and the density of soil composition decrease.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of various industrial chemical elements, which are used during the growing season of crops as fertilizers and means of protection against pests, is especially actively (Kolisnyk et al, 2019;Tsyhanskyi et al, 2019). The results of research by many scientists shown that the species and quantitative composition of the microflora changes significantly with increasing or decreasing the depth of tillage, replacement of moldboard plowing on boardless tillage, application of different types of fertilizers, their ratio and quality composition (Zvyagintsev, 1987;Karpenko et al, 2019;Radchenko et al, 2018;Mishchenko et al, 2017). Based on the above, the development of efficient and environmentally balanced cultivation technologies and the entire agricultural system in specific conditions in general is closely related to the study of rational integration of one of its most important parts -tillage of soil and fertilization of crops (Iutinskaya, 2006;Pyrog, 2004).…”
Section: Introductionmentioning
confidence: 99%